Health professionals' perspectives on exercise referral and physical activity promotion in primary care: Findings from a process evaluation of the National Exercise Referral Scheme in Wales. (November 2015) - Din, Nafees U; Moore, Graham F; Murphy, Simon; Wilkinson, Clare; Williams, Nefyn H
Background and objectives: Referring clinicians' experiences of exercise referral schemes (ERS) can provide valuable insights into their uptake. However, most qualitative studies focus on patient views only. This paper explores health professionals' perceptions of their role in promoting physical activity and experiences of a National Exercise Referral Scheme (NERS) in Wales. Design: Qualitative semi-structured group interviews. Setting: General practice premises. Methods: Nine semi-structured group interviews involving 46 health professionals were conducted on general practice premises in six local health board areas. Purposive sampling taking into account area deprivation, practice size and referral rates was employed. Interviews were transcribed verbatim and analysed using the Framework method of thematic analysis. Results: Health professionals described physical activity promotion as important, although many thought it was outside of their expertise and remit, and less important than other health promotion activities such as smoking cessation. Professionals linked decisions on whether to advise physical activity to patients to their own physical activity levels and to subjective judgements of patient motivation. While some described ERS as a holistic alternative to medication, with potential social benefits, others expressed concerns regarding their limited reach and potential to exacerbate inequalities. Barriers to referral included geographic isolation and uncertainties about patient selection criteria, medico-legal responsibilities and a lack of feedback about patient progress. Conclusion: Clinicians' concerns about expertise, priority setting and time constraints should be addressed to enhance physical activity promotion in primary care. Further research is needed to fully understand decision making relating to provision of physical activity advice and use of ERS.